El seminario de investigación y su relación con las diferentes metodologías y estrategias de enseñanza aprendizaje (2008)
ABSTRACT: this Article shows the way how it develops a seminar of research and the relations with different strategies and methodologies of learning and teaching used in the seminar. Methodology: the research was made during 2004-2005 in two seminars of research in the Nursing Faculty of the University of Antioquia. It used an the focalized type of the ethnographic methodology, emphasizing the observation in the groups of students and the two professors that coordinated the seminars. The information was gathered using three strategies: Revision of documented sources, in depth interviews with students and professors, observation. Results: it was found that the seminar its designed starting from a formal structure, where the professor organize the contents according to the needs that he assume the environment has concerning to the research and how he expect the student face the situation. Conclusions: the research seminar it´s designed and Developer from a procedural structure that privilege the contents that comes from the methods and the technic of research. The way how the participants of the process of learning and teaching interact makes stronger the procedural character of this.